Analisis Kemampuan Manajemen Biaya Dalam Perusahaan Jasa Konstruksi CV Pedalaman Raya Indah Nanga Bulik - Tonich Uda; Rinto Alexandro; Anggreini Talenta (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
The ability to manage cost in order to increase company productivity is a must. This ability is used in implementation of cost management function. There are three cost management functions, namely determining costs, assisting in decision making and activating financial reporting. The purpose of this study is to analyze the implementation of cost management functions in construction companies. This research was conducted by analyzing the comparison of the cost budget with the realization in the meeting building construction work packages in the CV Pedalaman Raya Indah construction company in 2019.  The results of the study concluded that the company had implemented the cost management function well. The cost management function consists of 3 things, namely determining costs, helping decision making and activating financial reporting. In determining costs, companies have been able to determine the costs appropriately. The total budget is smaller with its realization. This happens because the company's ability to determine costs appropriately and the existence of cost savings so that in its realization, the costs incurred do not exceed the budget that has been prepared. From the implementation of the cost management function that has been carried out, the company CV Pedalaman Raya Indah gained a profit of 27.81%.